Role of histone H3 lysine 27 methylation in Polycomb-group silencing. - Cao, R.; Wang, L.; Wang, H.; Xia, L.; Erdjument-Bromage, H.; Tempst, P.; Jones, R.S.; Zhang, Y. (Science, 2002)
Polycomb group (PcG) proteins play important roles in maintaining the silent state of HOX genes. Recent studies have implicated histone methylation in long-term gene silencing. However, a connection between PcG-mediated gene silencing and histone methylation has not been established. Here we report the purification and characterization of an EED-EZH2 complex, the human counterpart of the Drosophila ESC-E(Z) complex. We demonstrate that the complex specifically methylates nucleosomal histone H3 at lysine 27 (H3-K27). Using chromatin immunoprecipitation assays, we show that H3-K27 methylation colocalizes with, and is dependent on, E(Z) binding at an Ultrabithorax (Ubx) Polycomb response element (PRE), and that this methylation correlates with Ubx repression. Methylation on H3-K27 facilitates binding of Polycomb (PC), a component of the PRC1 complex, to histone H3 amino-terminal tail. Thus, these studies establish a link between histone methylation and PcG-mediated gene silencing.